Physical demands of a national U20 rugby team in international tournaments - Rodríguez-Rosal, M.; Armengod-Fernández, H.; Álvarez-Portillo, M.; Mancha-Triguero, D. (Journal of Human Sport & Exercise, 2026)
The quantification of the load in rugby is an activity that has been carried out for some years. However, after reviewing the literature, there is little information on the demands that players present in international tournaments. The objectives of this research were to characterize the demands of players in international tournaments, to find out if there were significant differences depending on the specific position (forwards or backs), the parts of the game (first or second half) or the type of tournament (European vs. World Cup). To do this, a national team was quantified during all the matches they played in a European tournament and in a world tournament. All the players analysed were from the Under 20 category (n = 32). Each player wore a Catapult Vector S7 inertial device. Different ANOVA analyses were performed. The results showed differences in most of the variables analysed depending on the playing position, the part of the game and the type of tournament. In addition, the results showed a greater demand in players with a Back position who participated in the European tournament. In the process of individualization, training programs should be tailored according to players' positions on the field and their specific demands.